Why the “Visitor Effect” Is Complicated. Unraveling Individual Animal, Visitor Number, and Climatic Influences on Behavior, Space Use and Interactions With Keepers—A Case Study on Captive Hornbills - Rose, Paul E.; Scales, Jake S.; Brereton, James E. (Frontiers in Veterinary Science, 2020)
A “visitor effect” on zoo-housed species has been documented since the 1970s, with research focused on mammals (specifically primates). To broaden our understanding of the “visitor effect” in a non-mammal, we conducted a case study on a pair of hornbills, recording behavior and aviary use alongside of visitor and keeper presence. Temperature and humidity were significant predictors of visitor number, and temperature was a better predictor of hornbill exhibit use than visitor presence. Behavior was significantly affected by the presence of keepers and individual variation in behavior was noted too. Visitor number mediated any interest in a keeper by birds: high visitor number decreased a bird’s interest in its keeper. Whilst we present a case study on a pair of birds, our research shows that any “visitor effect” is heavily influenced by other environmental variables and that different categories of human (i.e. visitor, caregiver) affect how zoo animals utilize their environment.